Effect of surface roughness on the oil distribution and the heat transfer coefficient for piston cooling gallery. (May 2022) - Hamza, Muhammad; Mei, Bing-Ang; Zuo, Zhengxing
Abstract: Piston cooling gallery plays a critical role in managing the temperature of the piston and its performance. This paper aims to study the effect of surface roughness on heat transfer coefficient (HTC) inside the cooling gallery. To do so, Eulerian multiphase model and the k-ε turbulence model were used for the oil and air flow through the cooling gallery. Dimples and protrusions were considered inside the cooling gallery for roughness. The results indicate that roughness elements distorted the oil distribution resulting in weaker oil slug formation and faster oil slug diffusion with the oil collected along the top or bottom wall. In addition, the average HTC for the walls was highly dependent on the jet impingement near the inlet. The average HTC didn't show much variation trend for the top and inner wall but there was prominent variation trend for the bottom and the outer wall. Moreover, vortex was observed within the dimple roughness element which resulted in rebounding effect leaving a trail of low HTC right behind the dimple roughness element. This was absent for protrusion roughness element. Finally, the oil flow across the protrusion led to higher local HTC compared with dimple roughness elements.